Resumption Sexual Intercourse After 6 Weeks Postpartum: an Islamic and Science Narrative Review - Ferina, Ferina; Indrayani, Diyan; Trisiani, Desi; H. Abdul-Mumin, Khadizah (Perhimpunan Intelektual Muslim Indonesia, 2024)
Islamic law has regulated postpartum sexual intercourse to be carried out after 40 days. In the perspective of reproductive health science, the average postpartum recovery occurs within 6 weeks. However, postpartum sexual health is still considered a minimally understood and taboo concept. It is often seen only from a physiological/biological point of view, and health workers also convey postpartum sexual health education as just a list of information that must be conveyed. The impact is increasing sexual complaints and problems as well as reproductive health problems, including unwanted pregnancies. This is a narrative review. data sources. The databases of PubMed, Elsevier, Sexual intercourse, and postpartum period were systematically searched, from their earliest dates, using a combination of key terms, including; 'sexual health', 'sexual intercourse', 'resumed', 'sexuality', 'sexual desire' 'postnatal' and 'postpartum', resulting in a final included dataset of 22 studies. Early resumed sexual intercourse in postpartum women is generally in healthy reproductive age (20-35 years), parity of one child, and history of vaginal delivery without complications. Readiness to return to sexual relations needs to be understood from the scientific aspect of health and Islamic law as educational material for the public.